Neuropsychiatric symptoms and altered sleep quality in cerebral small vessel disease - Li, Xi; Qin, Rong-Rong; Chen, Jian; Jiang, Hai-Fei; Tang, Pan; Wang, Yu-Jing; Xu, Dong-Wu; Xu, Tao; Yuan, Ti-Fei (Frontiers in Psychiatry, 2022)
Background: Sleep disturbances and neuropsychiatric symptoms are common clinical symptoms of cerebral small vessel disease (CSVD), but the underlying mechanism was unclear. Here we investigated the relationship between sleep quality and neuropsychiatric performances in patients with CSVD. Methods: A total of 30 CSVD patients and 35 healthy controls (HC) were recruited. Thirteen-item Beck Depression Inventory (BDI-13), Beck Anxiety Inventory (BAI), and Symptom Check List 90 (SCL90) were used to access depression, anxiety, and other psychological symptoms, respectively. Sleep quality was assessed by Pittsburgh Sleep Quality Index (PSQI), and cognitive function was tested by Montreal Cognitive Assessment (MoCA). Results: When compared to the healthy control group, patients with CSVD showed increased anxiety and neuropsychiatric symptoms, worsen sleep quality, and impaired cognition (p < 0.05). The prevalence of comorbid poor sleep quality in patients with CSVD was approximately 46%. CSVD patients with poor sleep quality also had more severe neuropsychiatric symptoms. After controlling demographic variables, sex and anxiety were significantly predicted sleep quality. Conclusions: The present study suggests that the prevalence of CSVD with poor sleep quality is high, sex and anxiety are independent risk factors for CSVD comorbid sleep quality.